(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: Introduzione - 1. Varietà di casi di titolarità dell’ufficio - 1.1. Casi di provvisione a vita dell’ufficio - 1.2. Casi di provvisione temporale dell’ufficio - 1.3. Uffici con limite massimo di età - 1.4. Motivi a favore della temporaneità delle nomine e della cessazione per età - 2. Novità del decreto del Dicastero per i Laici, la Famiglia e la Vita (3 giugno 2021) per quanto riguarda i limiti temporali del governo delle associazioni - 2.1 Aspetti generali della normativa - 2.2 Le motivazioni della norma - 2.3. Un profondo cambiamento nello spirito del diritto associativo ecclesiastico - 2.4. La necessaria sussidiarietà - 3. Conclusione. Time and age in the ecclesiastical office. The Decree of the Dicastery for Laity, Family and Life (June 3rd 2021) ABSTRACT: The article deals with the incidence of two factors in ecclesiastical offices: the passage of time and the fulfilment of certain age limits in the holder of the office. The first part of the study presents a systematic summary of the general legislation. The second part discusses the novelties and consequences of the treatment of the temporal factor of offices in the regulations published in 2021 by the Dicastery for Laity, Family and Life. The study concludes with an assessment of the norms of the Dicastery’s decree with regard to the fundamental freedom of association in the Church.